1992
DOI: 10.1038/eye.1992.104
|View full text |Cite
|
Sign up to set email alerts
|

Results of intraocular lens implantation in paediatric aphakia

Abstract: SUMMARYIntraocular lenses were implanted in 16 eyes of 13 patients with congenital cataract, and visual progress was plotted using a preferential-looking technique. Initial surgery was by lens aspiration with preservation of the posterior capsule, and subsequent posterior capsulotomy without anterior vitrectomy. Poly-HEMA posterior chamber lenses were used, usually as a primary pro cedure but in four cases as a secondary procedure after contact lens failure. No serious complications were encountered. Most ey e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…IOLs are now the standard optical treatment for older children after cataract surgery. Although their use during infancy is still controversial, our results confirm the findings of other studies, 31,32 which have shown that modern surgical techniques and instrumentation have made it technically feasible to implant an IOL in an infantile eye.…”
Section: Journal Of Aapos Volume 9 Number 3 June 2005supporting
confidence: 94%
See 1 more Smart Citation
“…IOLs are now the standard optical treatment for older children after cataract surgery. Although their use during infancy is still controversial, our results confirm the findings of other studies, 31,32 which have shown that modern surgical techniques and instrumentation have made it technically feasible to implant an IOL in an infantile eye.…”
Section: Journal Of Aapos Volume 9 Number 3 June 2005supporting
confidence: 94%
“…37 Oliver et al 2 found an opacification rate of 44% in infants and juveniles in the first 3 months after in-the-bag IOL implantation with an intact posterior capsule. Knight-Nanan et al 6 and Markham et al 31 reported PCO in 95.8% and 87.5% of cases, respectively. In our series, we found a gradual increase in PCO over the course of time.…”
Section: Journal Of Aapos Volume 9 Number 3 June 2005mentioning
confidence: 97%
“…Glasses get lost or broken, and are difficult to fit on infants and young children. Following encouraging reports of the use of hydrogel intraocular lenses in children,3 Kikuyu Eye Unit started to use lens implants for paediatric cataracts as a routine from 1993. This report is a retrospective study of the experience over the past 5 years.…”
mentioning
confidence: 99%
“…9 Surgeons were initially hesitant to implant adult-size and quality IOLs in the pediatric age group until a number of studies began to show their safety and efficacy in children. [11][12][13] Rigid PMMA lenses were initially predominantly used and are still used by a minority of surgeons. 14 However, soft, foldable IOLs facilitated small incision cataract surgery and are now the lens of choice for most surgeons.…”
Section: Historic Perspectivementioning
confidence: 99%